High-performance supercapacitor electrode based on naphthoquinone-appended dopamine neurotransmitter as an efficient energy storage material. (4th March 2021) - Biradar, Madan R.; Salkar, Akshay V.; Morajkar, Pranay P.; Bhosale, Sheshanath V.; Bhosale, Sidhanath V.
Abstract : NQ-DP based organic material was successfuly synthesized and employed as an efficient pseudocapacitor material. Abstract : Pseudocapacitors (PCs) have attracted research interest not only due to their superior performance in energy storage devices, but also to bridge the performance gap between batteries and electrostatic double-layer capacitors. Nevertheless, the storage of charges within PCs greatly depends on the electrode materials. Recent studies have found redox organic materials to be highly advantageous over conventional inorganic electrode materials due to their improved cycling stability augmented with electrochemical reversibility. In this work, we report a new organic electrode material, i.e., 2-((3, 4-dihydroxyphenethyl)amino)naphthalene-1, 4-dione (NQ-DP) composed of core naphthoquinone (NQ) and functionalised on the periphery with a dopamine (DP) neurotransmitter subunit. Following the fabrication of the electrode on toray carbon paper (CP), NQ-DP/CP displayed efficient pseudocapacitor performance for the three-electrode system with a very good specific capacitance of 177.9 F g −1 at a scan rate of 5 mV s −1 measured with cyclic voltammetry (CV), and 160.8 F g −1 at a current density of 0.5 A g −1 measured using galvanostatic charge–discharge (GCD) studies. Moreover, symmetric and asymmetric two electrode devices were fabricated using NQ-DP/CP electrode materials, which displayed a good specific capacitance of 43.4 F g −1 and 65.9 F g −1 at a current density of 0.5 A g −1 (GCD), respectively. NQ-DP/CP devices demonstrate an excellent capacitance retention percentage of >90% for over 5000 continuous charge–discharge cycles. Importantly, the NQ-DP/CP electrode displays an energy density of 6.0 W h kg −1 and 2.6 W h kg −1 at power densities of 0.6 kW kg −1 and 6.3 kW kg −1, respectively, in the symmetric cell combination. Energy densities of 9.0 W h kg −1 and 5.5 W h kg −1 were obtained at power densities of 1.0 kW kg −1 and 7.4 kW kg −1, respectively, in the asymmetric cell combination. Overall, the organic electrode architecture design and synthesis based on NQ and DP results in an outstanding pseudocapacitor energy storage device performance, and may open new routes for the production of high performance supercapacitors in the future.